THE EFFECT OF SPECIAL MENTAL ROTATION EXERCISES ON THE ACCURACY OF THE SMASH SERVE IN VOLLEYBALL FOR YOUNG PEOPLE - M.D. Ghaith Amir Abboud; M.D Farah Falah Hassan (Proximus Journal Publishing, 2025)
The space ball game contains many skills that lead to the team winning if it performs it with the required accuracy. After that, you must seek to acquire the decisive knowledge as it can be obtained directly, and as a result of the development in the skill performance in this game, experts and trainers to stimulate a modern skill exercise, and this skill is characterized by excellent and complex difficulty, and requires excellence in skill performance when performing. The crushing serve with the ball.
Keywords: performing; acquire; skills; winning